2021
DOI: 10.26905/jkdp.v25i2.5528
|View full text |Cite
|
Sign up to set email alerts
|

Earning Quality Effect on Stock Returns: GCG and CSR Mechanism

Abstract: This study explores the effect of corporate governance mechanisms and disclosure of corporate social responsibility on earnings quality and the effect on stock returns. The mining sector research analysis is indexed on the Indonesia Stock Exchange for the period 2014 to 2018. The research method used is causal research, with the analysis method used is multiple linear regression. The sampling technique used purposive sampling. The results showed that Managerial Ownership, Institutional Ownership, Independent C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The statistical tests showed that CSR has a positive effect on sharia compliance but has no effect on financial performance and maqashid sharia performance. It is in line with (D. P. Sari & Setiyawati, 2021) that CSR disclosure did not affect earnings quality. ( 2021) also states that CSR disclosure did not affect earnings quality based on conservatism.…”
Section: The Influence Of Corporate Social Responsibility (Csr) On Pe...supporting
confidence: 88%
“…The statistical tests showed that CSR has a positive effect on sharia compliance but has no effect on financial performance and maqashid sharia performance. It is in line with (D. P. Sari & Setiyawati, 2021) that CSR disclosure did not affect earnings quality. ( 2021) also states that CSR disclosure did not affect earnings quality based on conservatism.…”
Section: The Influence Of Corporate Social Responsibility (Csr) On Pe...supporting
confidence: 88%
“…However, the results of other studies did not find the same thing, where the supervisory function performed by independent commissioners had no discernible impact on earnings quality. (Arisanti, 2019;Kristian and Siswanto, 2022;Permata Sari and Setiyawati, 2021;Rucita and Sanjaya, 2021), This is usually due to the need for more supervisory functions carried out by independent commissioners.…”
Section: Introductionmentioning
confidence: 99%